The Relationship Of Organizational Competition Orientation, Marketing Capability And Customer Networks In Achieving Seller Achievement - Stivenes Tjin Siam; Heriyadi Heriyadi; Jamal Abdul Nassir Shaari (European Journal of Business and Management Research, 2024)
This study is to determine the role of organizational competition orientation and its effect on salesperson achievement. The relationship between variables consisting of four constructs namely Organizational Competition Orientation, Marketing Capability, Customer Networking and Salesperson Achievement were analyzed using four hypotheses. The data was processed by Structural Equation Modeling (SEM) with the Amos model. The sample consisted of 200 sales from various fields of distributor companies in West Kalimantan. The results showed that Organizational Competition Orientation had a significant effect on Marketing Capability, Marketing Capability had a significant effect on Customer Networking, Marketing Capability had a significant effect on Salesperson Achievement and Customer Networking had a significant effect on Salesperson Achievement.